2015
DOI: 10.1186/s40639-015-0013-4
|View full text |Cite
|
Sign up to set email alerts
|

Student empathy levels across 12 medical and health professions: an interventional study

Abstract: Background: Empathy is a difficult characteristic to define, teach and assess; the 'nebulous' properties of empathic behaviour often means that educators fail to incorporate the explicit teaching and assessment of empathy within the curriculum. One solution suggested is that teaching empathy in an interprofessional education setting is an effective educational approach in developing empathic behaviours. Method: Student participants from Monash University, Deakin University, University of South Australia, and E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
2
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 41 publications
(53 reference statements)
6
31
2
12
Order By: Relevance
“…18,19 Standing at the next ranks, the relative scores Our finding that female physicians express higher level of empathy compared with their male counterparts is congruent to several previous studies from various countries. 9,10,[21][22][23] We also observed that physicians with main specialties (internal medicine, obstetrics, and pediatrics specialties) are more empathic toward the patients compared with other physicians. In addition, the level of empathy was found to be higher among physicians with human-centric specialties.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…18,19 Standing at the next ranks, the relative scores Our finding that female physicians express higher level of empathy compared with their male counterparts is congruent to several previous studies from various countries. 9,10,[21][22][23] We also observed that physicians with main specialties (internal medicine, obstetrics, and pediatrics specialties) are more empathic toward the patients compared with other physicians. In addition, the level of empathy was found to be higher among physicians with human-centric specialties.…”
Section: Discussionmentioning
confidence: 64%
“…Age, fertility, and severity of EH in histology are the most important factors determining the treatment option [5]. Most studies have addressed hysterectomy in patients with atypical EH [5], particularly those with PCOS, and have led to conflicting results [5][6][7][8][9][10][11].…”
Section: Background and Objectivesmentioning
confidence: 99%
“…Therefore, medical schools may need to pay attention Possible explanation for the highest score observed for "perspective taking" and "compassionate care" subscales might be communication skills training program given in the 2 nd year. There are many studies that shows empathy can be enhanced by effective educational strategies, targeted educational programs, or medical consultations with SPs (Aspegren, 1999;Winefield and Chur-Hansen, 2000;Stepien and Baernstein 2006;Fernandez Olano et al, 2008;Batt Rawden et al, 2013;Hojat et al,2013;Kelm et al, 2014;Schweller et al, 2014;Williams et al;. Williams et al (2015) has shown that self-reported empathy levels have been shown to improve following DVD simulation-based workshops.…”
Section: Discussionmentioning
confidence: 99%
“…It is strongly argued that the attitudes and practices that deaden empathy need to be removed, and that empathy needs to be retaught to those who have lost it (Hojat et al 2009;Khanuja et al 2011;Pedersen 2010;Singh 2005;Williams et al 2015). Empathy training needs to be introduced as part of the curriculum so that it is perceived by students as a useful skill to be fostered, rather than an extraneous skill that can be neglected.…”
Section: The Benefits Of Empathy For Patients and Physiciansmentioning
confidence: 99%